OFFSET
1,3
COMMENTS
FORMULA
Conjecture: a(n) = 2*a(n-1)+6*a(n-2)-2*a(n-3)-a(n-4). G.f.: -x*(x+1)*(3*x-1) / (x^4+2*x^3-6*x^2-2*x+1). [Colin Barker, Jan 17 2013]
EXAMPLE
MATHEMATICA
q[x_] := x + 1; d = Sqrt[x + 2];
p[n_, x_] := ((x + d)^n + (x - d)^n )/ 2
(* similar to polynomials defined at A161516 *)
Table[Expand[p[n, x]], {n, 0, 4}]
reductionRules = {x^y_?EvenQ -> q[x]^(y/2),
x^y_?OddQ -> x q[x]^((y - 1)/2)};
t = Table[Last[Most[FixedPointList[Expand[#1 /. reductionRules] &, p[n, x]]]], {n, 0, 30}]
Table[Coefficient[Part[t, n], x, 0], {n, 1, 30}]
(* A192346 *)
Table[Coefficient[Part[t, n], x, 1], {n, 1, 30}]
(* A192347 *)
CROSSREFS
KEYWORD
nonn
AUTHOR
Clark Kimberling, Jun 28 2011
STATUS
approved